Social and Seasonal Factors Contribute to Shifts in Male African Elephant (Loxodonta africana) Foraging and Activity Patterns in Kruger National Park, South Africa - Kara du Plessis (MDPI AG, 2021)
African savannah elephants (Loxodonta africana) are well-known as ecosystem engineers with the ability to modify vegetation structure. The present study aimed to examine how male elephant foraging behaviour is affected across (a) season (wet versus dry); (b) time of day (before or after noon); (c) presence or absence of other elephants; and (d) reproductive state (musth versus no musth). Six radio-collared adult elephant bulls were observed twice per week from June 2007–June 2008 in Kruger National Park (KNP), South Africa. Using generalized linear mixed effect modeling, results indicate that elephant bulls graze more during the wet season and browse more during the dry season. To potentially offset the costs associated with thermoregulation during the heat of the day, KNP elephants spent more time foraging during the morning, and more time resting during the afternoon. Male elephants also foraged significantly less when they were associated with females compared to when they were alone or with other males. This is likely due to male–female associations formed mainly for reproductive purposes, thus impeding on male foraging behaviours. In contrast, the condition of musth, defined by the presence of related physical signs, had no significant effect on foraging behaviour.